2022
DOI: 10.1177/01650254211064352
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic change meets mechanisms of change: Examining mediators in the latent change score framework

Abstract: Researchers in behavioral sciences are often interested in longitudinal behavior change outcomes and the mechanisms that influence changes in these outcomes over time. The statistical models that are typically implemented to address these research questions do not allow for investigation of mechanisms of dynamic change over time. However, latent change score models allow for dynamic change (not just linear or exponential change) over time and have flexibility in parameter constraints that other longitudinal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To explore the developmental and multivariate quality of dynamic processes of L2 affective variables, appropriate statistical models are required to represent the process in which previous phenomena have prospective outcomes and the processes of variation can be constantly influenced by external and internal factors. LCS models used in the current study are flexible and adaptable enough to examine developments in longitudinal investigations (Cancer et al, 2021;Hilley & O'Rourke, 2022). On the whole, the findings showed that the quantity (i.e., the decreasing and increasing trend) and quality (i.e., the acceleration and deceleration of rate of change) of one L2 affective variable can increase the patterns of change of other related affective variables over time.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…To explore the developmental and multivariate quality of dynamic processes of L2 affective variables, appropriate statistical models are required to represent the process in which previous phenomena have prospective outcomes and the processes of variation can be constantly influenced by external and internal factors. LCS models used in the current study are flexible and adaptable enough to examine developments in longitudinal investigations (Cancer et al, 2021;Hilley & O'Rourke, 2022). On the whole, the findings showed that the quantity (i.e., the decreasing and increasing trend) and quality (i.e., the acceleration and deceleration of rate of change) of one L2 affective variable can increase the patterns of change of other related affective variables over time.…”
Section: Discussionmentioning
confidence: 80%
“…LCS models mix several dimensions of autoregressive and latent growth models (LGMs;McArdle, 2009). The LCS approach facilitates the measurement of within-individual variation between two or more points of time as the target outcome by developing latent constructs that reflect the variation in true scores between the two measurement times, t -1 and t (Hilley & O'Rourke, 2022).…”
Section: The Latent Change Score Methodsmentioning
confidence: 99%
See 1 more Smart Citation